Optimized State Model of Piecewise-Linear Dynamical Systems - Pospisil, Jiri; Kolka, Zdenek; Hanus, Stanislav; Michalek, Vaclav; Brzobohaty, Jaromir (Radioengineering Society, 2003)
The conditions for an optimized design of the second dynamical system having low eigenvalue sensitivities are directly derived. Their more general form is in accordance with the previous results obtained by using linear topological conjugacy.
Keywords: Dynamical systems; piecewise-linear systems; sensiti-vity; optimization